3 - Émigration, culture et mutations sociales : étude de cas du sud-est de la Tunisie – la région de Zarzis - Hafedh, Ben Amor (Africa Development, 2021)
Immigration has become a phenomenon that is deeply rooted in the collective thinking and individual behavior of citizens of poor countries. It is viewed as a natural response to unfavorable conditions, and a reaction to an unbalanced economic system, in addition to a policy of social exclusion that has evolved slowly over time and that has failed to cope with the demographic boom in countries in southern Mediterranean. In this perspective, we intend to assess the socio-cultural impact of this departure movement. The paper focuses on the distinction between the human capital, as represented in the migrant, and the repercussions of his movement, that are both qualitative and cumulative. The ultimate focus of our analysis is on the effects of this migration on women, the family and their social values.